2019
DOI: 10.1038/s41380-018-0330-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influences on structural brain measures in twins with autism spectrum disorder

Abstract: Atypical growth patterns of the brain have been previously reported in autism spectrum disorder (ASD) but these alterations are heterogeneous across individuals, which may be associated with the variable effects of genetic and environmental influences on brain development. Monozygotic (MZ) and dizygotic (DZ) twin pairs with and without ASD (aged 6–15 years) were recruited to participate in this study. T1-weighted MRIs (n = 164) were processed with FreeSurfer to evaluate structural brain measures. Intra-class c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 66 publications
0
23
0
Order By: Relevance
“…Recently, Hegarty et al ( 2019 ) observed greater environmental influences on some aspects of brain morphometry (cortical thickness and cerebellar white matter volume) in twins with ASD than in normal twins; however, most of the observed effects were attributable to shared rather than non-shared environment. The latter dominated our observations and could encompass epigenetic changes, random developmental (in utero) or environmental (extrauterine) perturbations, or the effects of somatic mutations, to which affected individuals might be more vulnerable than unaffected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Hegarty et al ( 2019 ) observed greater environmental influences on some aspects of brain morphometry (cortical thickness and cerebellar white matter volume) in twins with ASD than in normal twins; however, most of the observed effects were attributable to shared rather than non-shared environment. The latter dominated our observations and could encompass epigenetic changes, random developmental (in utero) or environmental (extrauterine) perturbations, or the effects of somatic mutations, to which affected individuals might be more vulnerable than unaffected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Aguiar et al, 0000 , Amare et al, 0000 , Avramopoulos et al, 0000 , Braden and Riecken, 2019 , Brown and Derkits, 2010 , Crespi and Go, 2015 , Creusot et al, 2002 , D'Antonio et al, 0000 , Dendrou et al, 2018 , Psychiatry, 2012 , Eberhard et al, 0000 , Gambino et al, 2018 , Goddard et al, 2007 , Guerini et al, 2018a , Guerini et al, 2018b , Guerini et al, 2019 , Greenig, 0000 , Hegarty et al, 2020 , IMGT, 2020 , Jeppesen and Benros, 2019 , Jézéquel et al, 2017 , Khandaker et al, 2017 , Mackay et al, 2000 , Le Clerc et al, 2015 , Levman et al, 0000 , Limphaibool et al, 2019 , Meltzer, 0000 , Mokhtari and Lachman, 0000 , Pereira et al, 0000 , Perron et al, 2012 , Purcell et al, 2009 , Ripke et al, 2014 , Shah et al, 2019 , Shi et al, 2009 , Stefansson et al, 2009 , Sterner et al, 0000 , Tamouza et al, 2020a , Tamouza et al, 2020b , Verhelst et al, 2011 , Yudofsky, 2009 .…”
Section: Uncited Referencesmentioning
confidence: 99%
“…ASD is more than three times more common in males than in females [6]. Even though a specific etiology can be identified in some individuals with ASD, most of the variation in ASD risk is believed to have its origin in a complex interaction between genetic and environmental factors [7][8][9]. The occurrence of ASD has increased over the past three decades, partly reflecting changes in diagnostic criteria and increased awareness [5].…”
Section: Introductionmentioning
confidence: 99%